Availability of self-care products for sexual and reproductive health provided by community pharmacists in Rwanda: A cross-sectional study - Samuel Ndayishimye; Adesina Oladokun; Marie Francoise Mukanyangezi; Jean Claude Hategekimana (Taylor & Francis Group, 2024)
Access to and use of sexual and reproductive health (SRH) services remain a global public health concern, particularly in developing countries. This study aimed to understand the attitudes and perceptions of pharmacists in Rwandan community pharmacies and to assess the availability of sexual and reproductive health products in these pharmacies.In a cross-sectional study conducted in Rwanda from 1 September 2023 to 30 November 2023, registered and licensed pharmacists from 864 community pharmacies were surveyed, employing a quantitative research approach. Systematic sampling was used to collect the data. A chi-square test was conducted for relationships between variables.SRH products for self-care were widely available in Rwandan community pharmacies, ranging from 82.3% to 97.3%, except for ovulation tests (28.4%). Chi-square tests indicated that married pharmacists were more likely to provide educational guidance on SRH products (χ2 =  8.81, P-value = 0.012). Community pharmacists had positive attitudes and self-reported confidence in dispensing and providing education to pharmacy-based SRH users.The Rwandan community pharmacies had extensive availability of SRH products for self-care use. Pharmacists in these pharmacies had positive attitudes and self-reported confidence in dispensing and guiding the community on SRH products. Continuous professional training is recommended to enhance the quality and standards of SRH.